2017
DOI: 10.1039/c7ta00220c
|View full text |Cite
|
Sign up to set email alerts
|

A novel K-ion battery: hexacyanoferrate(ii)/graphite cell

Abstract: The four volt K-ion battery is demonstrated as a possible alternative to 4 volt Li-ion battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
513
3
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 440 publications
(559 citation statements)
references
References 41 publications
28
513
3
5
Order By: Relevance
“…Note that in the first few charge cycles, more than the theoretical capacity (≈155 mA h g −1 ) was achieved, possibly due to parasitic reactions with the electrolyte and/ or electrochemical dehydration, as often observed in Prussian blue analogues. [88] Two distinct plateaus were observed during charge (4.05 and 4.1 V) and discharge (3.85 and 4 V) with a small voltage step. Xue et al suggested that the low-voltage plateau originates from a low-spin Fe 2+/3+ redox reaction, whereas the high-voltage plateau reflects a high-spin Mn 2+/3+ reaction.…”
Section: Hexacyanometallate Groups (Prussian Blue Analogues)mentioning
confidence: 99%
See 4 more Smart Citations
“…Note that in the first few charge cycles, more than the theoretical capacity (≈155 mA h g −1 ) was achieved, possibly due to parasitic reactions with the electrolyte and/ or electrochemical dehydration, as often observed in Prussian blue analogues. [88] Two distinct plateaus were observed during charge (4.05 and 4.1 V) and discharge (3.85 and 4 V) with a small voltage step. Xue et al suggested that the low-voltage plateau originates from a low-spin Fe 2+/3+ redox reaction, whereas the high-voltage plateau reflects a high-spin Mn 2+/3+ reaction.…”
Section: Hexacyanometallate Groups (Prussian Blue Analogues)mentioning
confidence: 99%
“…[27,90] Overall, the specific energy achievable in K x Mn[Fe(CN) 6 ] 1−z -nH 2 O with the two-electron redox reaction rivals that of LiFePO 4 , though its volumetric energy density is unsatisfactory. [83,88] The full cell performance against the graphite anode shown in Figure 8b reveals excellent discharge rate capability, with delivery of 62 mA h g cathode −1 at a 2 A g cathode −1 rate.…”
Section: Hexacyanometallate Groups (Prussian Blue Analogues)mentioning
confidence: 99%
See 3 more Smart Citations